TELAAH MANAJEMEN SANGGAR BARABAH MANDI DESA WISATA KAMPUANG SARUGO KABUPATEN LIMA PULUH KOTA - Yuhari Andrika; Hamidun Syaputra; Ediwar Ediwar; Rasmida Rasmida (Journal of Innovation Research and Knowledge, 2023)
Barabah Mandi community is a group based in the tourism village of Kampuang Saribu Gonjong (Kampuang Sarugo), Sungai Dodok, Lima Puluh Kota regency, West Sumatra. Established for last 3 decades with a management and management concepts that have evolved over time. Finally, the Barabah Mandi group was active in as like with the rapid development of the name Kampuang Saribu Gonjong. In this paper, we will discuss about management, existence and developments in the Barabah Mandi group, namely: planning, organizing, actuating, and controlling. No doubt, Kampuang Sarugo won its golden age by winning second place in the Anugerah Pesona Indonesia 2020 for the Most Popular Traditional Village category, which made the general public start to look at it as an area with promising tourism potential. This was made possible by the contribution of the famous West Sumatran musician brothers, Alfalah, Moch. Hafiz and Wilda Aviva (adviser and current manager of the Barabah Mandi Group) as music illustrators for the videos that were contested